2007
DOI: 10.1088/1741-2560/4/4/007
|View full text |Cite
|
Sign up to set email alerts
|

Complex impedance spectroscopy for monitoring tissue responses to inserted neural implants

Abstract: A series of animal experiments was conducted to characterize changes in the complex impedance of chronically implanted electrodes in neural tissue. Consistent trends in impedance changes were observed across all animals, characterized as a general increase in the measured impedance magnitude at 1 kHz. Impedance changes reach a peak approximately 7 days post-implant. Reactive responses around individual electrodes were described using immuno- and histo-chemistry and confocal microscopy. These observations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
358
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(388 citation statements)
references
References 41 publications
26
358
0
Order By: Relevance
“…Impedance spectroscopy in a frequency range of 10 Hz-10 kHz (Figure 4, and Supplementary Fig. S3) showed that PC/COC/CPE fiber probes exhibit slightly decreasing impedance values of 1.3-2.8 ± 0.4 MΩ (for 10 mm) and 2-6 ± 2 MΩ (for 50 mm) at 10-1000 Hz (the frequency range most useful for recording of neuronal activity), which lies within the range commonly cited for neural probes [29,39,40] .…”
Section: Resultssupporting
confidence: 63%
“…Impedance spectroscopy in a frequency range of 10 Hz-10 kHz (Figure 4, and Supplementary Fig. S3) showed that PC/COC/CPE fiber probes exhibit slightly decreasing impedance values of 1.3-2.8 ± 0.4 MΩ (for 10 mm) and 2-6 ± 2 MΩ (for 50 mm) at 10-1000 Hz (the frequency range most useful for recording of neuronal activity), which lies within the range commonly cited for neural probes [29,39,40] .…”
Section: Resultssupporting
confidence: 63%
“…They are fabricated with silicon or titanium. They may comprise a single needle bearing multiple contacts on its shaft [20,39] or a 10 9 10 matrix of single contact electrodes [19,36]. Successful penetrating electrodes are already available to humans, e.g., cochlear implants [40] and deep brain stimulator [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…Once an electrode is implanted it will be treated as a foreign material by the body, but the material should not impact the immune system dramatically (Polikov et al, 2005). This kind of response would reduce the electrode charge delivery capacity and recording sensitivity (Williams et al, 2007). Biocompatibility of CNTs is highly dependent on their mode of production, size, purification chemical functionalization, dose, and type of administration (systemic etc) (Ciofani et al, 2010;Nayagam et al, 2011).…”
Section: Biocompatibiltymentioning
confidence: 99%